THE IMPACT OF GLOBALIZATION ON THE LANGUAGE OF YOUTH USING EXAMPLES OF ANGLICISMS (Scientific journal of the Fergana State University, 2025)
The article examines how globalization affects the language of youth. The reasons why Anglicisms are leading in the modern language of youth are naturally globalization and international interaction. English is one of the main languages of international communication, particularly in science and culture, business and politics. Anglicisms are a natural phenomenon that is difficult to stop in the context of globalization. The reasons why Anglicisms are leading in the modern language of youth are naturally globalization and international interaction. English is one of the main languages of international communication, in particular in science and culture, business and politics. For this reason, they actively penetrate the language of youth, and occupy a leading position. English is a universal, mass means of communication and many trends in politics, technology, and art originate in English-speaking countries.